Efforts to Increase Local Revenue with Local Tax Revenue Innovation, a Success Study of Tegal City - Mukhlis, Mukhlis; Nabilla, Shafa; Sumirah, Sumirah; Setiyanto, Adi Irawan (Politeknik Negeri Batam, 2024)
The success of the Tegal City Government to increase local revenue (PAD) can be a benchmarking for other local governments. Therefore, this study was aimed at describing and analyzing the innovations made by the Regional Finance Agency (BKD) of Tegal City in increasing local tax revenue in 2022-2023. The analysis used Roger's approach which includes four components: relative advantage, compatibility, complexity, and trialability. A qualitative research, this study used interviews, observation, and documentation to collect data, and the interactive model for data analysis. This study found three innovations made by the BKD of Tegal City: (1) electronification of local taxes, (2) Pick-up services for land and building tax (PBB) payments, and (3) tax-aware volunteers. The three innovations were successful and well accepted by the public because of giving benefits and convenience, meeting public need, and being practical to be done, tested and observed. Keywords: local revenue, local tax, innovation